HISTORICAL AND PEDAGOGICAL PROJECTION OF THE “TEACHING” PHENOMENON - Chumak, Mykola (Mountain School of Ukrainian Carpaty, 2020)
The content of the article problematizes the interdependence of the cognition and teaching processes, which is reproduced at the level of domestic historical and pedagogical research of previous periods. The significance of the cognition patterns impact on the productivity of learning is outlined; their absence makes it impossible to achieve educational goals. Through comparative analysis, emphasis is placed on the dogmatic centering of teaching in the Middle Ages, which in the course of progressive development gave way to explanatory and illustrative teaching. Emphasis is placed on the problematic nature of human knowledge "aging," caused by accelerated social progress, which necessitates the promotion of lifelong learning. Taking into account theoretical generalizations made it possible to compare interpersonal bilateral cooperation: teacher’s teaching and student’s learning. The historiosophical parallel between the cognitive activity of the student in the learning process and the scientific knowledge of the scientist-researcher according to the selected criteria has been made. A number of author's views on the problem of educational cognition are represented. Features of educational cognition are actualized, in particular: the possibility of mastering difficult issues; intensification of the learning process; search for new and unknown facts. The author's conclusions on the regularities of analytical-synthetic activity of students are represented, the transition from which enabled further theoretical structuring of visually effective, visually figurative and verbal-logical thinking. The toolkit for the study was historical and pedagogical, phased-problem, chronological-content and comparative methods. The use of a number of methodological tools made enabled to summarize that the phenomenon of "learning" "circulates" successfully at the level of basic structures - sensory and visual perception, which replaced unproductive learning. It is concluded that the existing historical experience of teaching today needs a systematic analysis and enrichment with new theoretical and methodological approaches that can reformat the existing educational reality into a highly productive educational process.